2019
DOI: 10.3390/w11020394
|View full text |Cite
|
Sign up to set email alerts
|

Water Quality Modeling of Mahabad Dam Watershed–Reservoir System under Climate Change Conditions, Using SWAT and System Dynamics

Abstract: The total phosphorus (TP) concentration, as the primary limiting eutrophication factor in the Mahabad Dam reservoir in Iran, was studied, considering the combined impacts of climate change, as well as the scenarios on changes in upstream TP loadings and downstream dam water allocations. Downscaled daily projected climate data were obtained from the Beijing Normal University Earth System Model (BNU-ESM) under moderate (RCP4.5) and extreme (RCP8.5) scenarios. These data were used as inputs of a calibrated Soil a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 49 publications
(15 reference statements)
2
28
0
2
Order By: Relevance
“…Runoff forecasting plays an essential role in flood mitigation management, agricultural water management, water transportations, and other socio-economical activities closely related to water resources. Many approaches, including physics-based models [1][2][3] and data-driven models [4][5][6], have been developed during recent decades to obtain a precise prediction result of the runoff.…”
Section: Introductionmentioning
confidence: 99%
“…Runoff forecasting plays an essential role in flood mitigation management, agricultural water management, water transportations, and other socio-economical activities closely related to water resources. Many approaches, including physics-based models [1][2][3] and data-driven models [4][5][6], have been developed during recent decades to obtain a precise prediction result of the runoff.…”
Section: Introductionmentioning
confidence: 99%
“…Jamali et al showed that lack of adaptation to climate variations leads to a considerable decrease in efficiency in Iran's Karkheh Hydropower in the future [51]. Some examples of a lack of insufficient climate assessment studies and improper managements in Iran are: damages caused by heavy rains; floods and damages on many houses, infrastructure, water and power supply; groundwater depletion; droughts and their impacts on food quality and quantity, economy, health, and people's livelihood; drying lakes; sand storms; and ecosystem degradation [52][53][54][55][56][57][58][59][60][61][62]. These issues indicate the necessity of implementing sustainable adaptation and mitigation plans, considering possible variations in climate.…”
Section: Resultsmentioning
confidence: 99%
“…(1) The RCPs climate scenario Due to space limitations, the RCPs climate scenario was selected to output precipitation and temperature series, and the 2001 to 2017 rate was periodically divided, and 2018 to 2050 was the forecast period. The precipitation and temperature were statistically analyzed and simulated in the RCP 2.6, RCP 4.5 and RCP 8.5 (as 1, 2 and 3) scenarios through the calibrated and down-scaled GFDL-ESM2M, HadGEM2-ES, IPSL-CM5A-LR, MIROC-ESM-CHEM, and NorESM1-M models (as a, b, c, d and e) from 2001 to 2017 [33]. If the data has uncertainty in the time of acquisition, or the time precision of the data is not met, then the validity of the spatio-temporal data cannot be explained, and reasonable reasoning cannot be made for the uncertain data in the data.…”
Section: Data Collection and Arrangementmentioning
confidence: 99%